SS-COP mutants show specific high sensitivity to chloride ions. (4th March 2021) - Sánchez-Simarro, Judit; Bernat-Silvestre, César; Aniento, Fernando; Marcote, María Jesús
ABSTRACT: Coat Protein I (COPI) consists of a complex (coatomer) formed by seven subunits (α-, β-, β'-, γ-, δ-, ε-, and ζ-COP) that is recruited to Golgi membranes to form vesicles that shuttle from the Golgi apparatus to the ER and between Golgi stacks. Recently, it has been described that loss of function mutants of the two Arabidopsis β-COP genes, β1-COP and β2-COP, showed increased sensitivity to salt stress (NaCl). Using a mixture of either Na + or Cl − salts, we have now found that β-COP mutants are specifically and highly sensitive to chloride ions.